Juridical Analysis and Problems of Regional Grant Implementation to the Central Government - Rosada, Hilman (Indonesian Journal of Multidisciplinary Science, 2026)
The provision of regional grants to the central government or vertical agencies is a normatively permissible financial instrument to support the implementation of government functions in the regions, but its implementation often undergoes administrative and substantive distortions. This study aims to analyze the juridical basis and map the problems of the implementation of grant expenditure using the literature study method through a normative juridical approach and an empirical juridical approach that is descriptive-analytical. The results of the study show that there is non-compliance with regulations, where grants that should be discretionary shift into routine obligations without clear urgency, and are often not in line with the stages of preparing the APBD. In addition, it was found that there was a potential overlap of funding with the State Revenue and Expenditure Budget (APBN) due to weak selection and verification instruments. As a strategic solution, this study recommends strengthening normative compliance through the establishment of strict Regional Head Regulations (Perkada), integration of fiscal capacity-based planning, digitalization of governance through the Regional Government Information System (SIPD) to reduce information asymmetry, and optimizing the role of the Government Internal Supervisory Apparatus (APIP) to ensure the principle of value for money and budget efficiency.